Pemanfaatan Limbah dan Sumber Daya Lokal dalam Pelatihan Pembuatan Pakan Ikan Mandiri untuk Kelompok KUPS Perikanan Desa Tuwung - Pasaribu, Marvin Horale; Ariefin, Mokhamat; Ompusunggu, Dicky Perwira; Saputra, Rızkı Rachmad; Agnestisia, Retno; Yuliana, Yuliana; Purba, Abed Nego; Prianus, Okta (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2025)
Tuwung Village, Pulang Pisau Regency, possesses significant potential in the fisheries sector. However, the development of this sector is hindered by the reliance on expensive commercial fish feed, which limits profit margins from fish sales. Furthermore, organic waste generated from agricultural and livestock activities remains underutilized, posing a potential environmental pollution problem. To address these challenges, a training program on independent fish feed production utilizing organic waste and local resources has been implemented. This program aims to equip the KUPS Fisheries Group in Tuwung Village with the knowledge and skills to produce high-quality fish feed at a more affordable cost. Through this training, participants were introduced to the concept of utilizing household vegetable waste and motan fish from Lake Sabuah as alternative feed ingredients. Additionally, they received training in both conventional and mechanical fish feed production processes, employing a specially designed mixer unit. The program outcomes indicate that participants successfully grasped the concept of waste and local resource utilization and are now capable of producing fish feed independently. It is anticipated that this program will enhance the productivity and efficiency of fish farming businesses in Tuwung Village, while simultaneously mitigating the environmental impact of organic waste.